The Lightning by Mobile Tech - Susila, Putu Agus Dharma (International Research Journal of Management, IT & Social Sciences, 2014)
According to the lightning protection requirements of the facilities and equipments in oil depot, this paper proposes the integrated mobile lightning protection device and technology to protect lightning strike in different regions of oil depot, analyses the systemic composition and the technical characteristics of the integrated mobile lightning protection device and technology, and practically applies them to establish the lightning protection system in the important region of oil depot. The application shows that the integrated mobile lightning port According to the lightning protection requirements of the facilities and equipment in oil depot, this paper proposes the integrated mobile lightning protection device and technology to protect lightning strike in different regions of oil depot, analyses the systemic composition and the technical characteristics of the integrated mobile lightning protection device and technology, and practically applies them to establish the lightning protection system in the important region of oil depot. The application shows that the integrated mobile lightning protection device and technology are safe, reliable, practical and convenient, which makes it suitable for widely applications.